L’homélie sur la foi en la Trinité de Sévérien de Gabala (traduction française annotée) - Colin, Gerard (Aethiopica, 2003)
The texts of the first period of the Ethiopic literature, immediately translated from Greek, are among the finest of the geʿez production. They are also most difficult, due to the specificity of both languages. The Homily on the Trinity of Severian of Gabala is no doubt the most noteworthy and anduous one of this corpus. The French annotated translation given here tries to explain all the difficulties and obscurities, in respect only of the Ethiopic, of it.